2012
DOI: 10.1515/cclm-2011-0085
|View full text |Cite
|
Sign up to set email alerts
|

The new Roche Vitamin D Total assay: fit for its purpose?

Abstract: The new Elecsys assay fulfilled present analytical performance requirements and showed close agreement to other well-established methods for 25(OH)D analysis, making it fit for routine assessment of vitamin D status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 0 publications
4
17
0
Order By: Relevance
“…Other recent publications based on the Elecsys assay have confirmed that the assay has good precision and accuracy, and shows close agreement to other wellestablished methods for 25-OHD analysis, making it very suitable for routine assessment of vitamin D status (32,36,39,40). In conclusion, the Elecsys assay demonstrated low imprecision, high sensitivity, good lot-to-lot consistency, as well as good overall agreement with measurements obtained using LC-MS/MS and HPLC methods.…”
Section: Discussionsupporting
confidence: 69%
“…Other recent publications based on the Elecsys assay have confirmed that the assay has good precision and accuracy, and shows close agreement to other wellestablished methods for 25-OHD analysis, making it very suitable for routine assessment of vitamin D status (32,36,39,40). In conclusion, the Elecsys assay demonstrated low imprecision, high sensitivity, good lot-to-lot consistency, as well as good overall agreement with measurements obtained using LC-MS/MS and HPLC methods.…”
Section: Discussionsupporting
confidence: 69%
“…These findings obtained for the whole group showed variable concordance with other studies and were compatible with recent studies on the performance of the Architect and Cobas systems. 35,36 These regression analysis results were also comparable with the results reported by Ong et al In another comparison study conducted by Farrel et al, both the Architect and the Cobas systems exhibited dissimilar results. 37,38 Heijboer et al evaluated the influence of DBP on the accuracy of the assays and found better results for the Cobas system and worse results for the Architect system using healthy individuals.…”
Section: Discussionsupporting
confidence: 87%
“…Vitamin D deficiency was defined as ⩽20 ng/ml while vitamin D insufficiency is recognized as 21-29 ng/ml. The recommended level for vitamin D is ⩾30 ng/ml [Emmen et al 2012].…”
Section: Methodsmentioning
confidence: 99%